Energy bandgap engineering of ZnO using impurity elements for solar cell applications: a DFT study - Ul Haq, Bakhtiar (Trans Tech Publications, Switzerland, 2014)
As a transparent conducting oxide, Cd:ZnO system is considered potential candidate for optoelectronic applications alternate to Al:ZnO. However instability issue of the Cd:ZnO system is under debate. Here we investigate effect of Cd impurities on physical properties of ZnO in wurtzite (WZ) as well as zincblende (ZB) geometries. Density functional theory (DFT) based full potential linearized augmented plane wave plus local orbital FP-L(APW+lo) method has been adapted for these investigations. To calculate the total energy of the system, exchange correlation energy term is evaluated at the level of GGA. For the more realistic band gap calculation, GGA in addition to mBJ exchange potential has been employed. From our calculations, it is observed, Cd:ZnO is more stable in ZB structure than that of WZ. The Cd substitution ZnO has a tendency to convert the hexagonal geometry into cubic. It is also observed, doping of the Cd impurities strongly influence the electronic structures resulting into the narrowing energy band gap.